Frugivoria em morcegos (Mammalia, Chiroptera) no Parque Estadual Intervales, sudeste do Brasil - Passos, Fernando C. (2003)
This study was carried out at the Intervales State Park, an Atlantic Rain Forest area in Southeastern Brazil. Bats were monthly mist netted over a full year, and fecal samples were collected for dietary analysis. The seeds found in each sample were identified in the laboratory under a stereoscopic microscope by comparison with seeds taken from ripe fruits collected in the study area. Three hundred and seventy one bats were collected, of which 316 (85.2%) were frugivorous. The total number of fecal samples with seeds and/or pulp was 121. Sturnira lilium (E. Geoffroy, 1810) was the most abundant species in the study area (n = 157 captures) and Solanaceae fruits accounted for 78.5% of the fecal samples with seeds (n = 56). Artibeus fimbriatus Gray, 1838 (n = 21 samples) fed mostly on Cecropiaceae (38%) and Moraceae fruits (24%), and Artibeus lituratus (Olfers, 1818) (n = 7 samples) on Cecropiaceae (57%) and Moraceae (29%). Carollia perspicillata (Linnaeus, 1758) (n = 16 samples) fed mostly on Piperaceae fruits (56,3%), but Solanaceae (31,3%) and Rosaceae seeds (12,5%) were also found in feces. Overall, seeds found in bat feces belong to eight plant families: Solanaceae (n = 67 samples); Cecropiaceae (n = 14); Piperaceae (n = 14); Moraceae (n = 8); Rosaceae (n = 3); Cucurbitaceae (n = 3); Cluseaceae (n = 1), and Araceae (n = 1). The close association of different bat species with fruits of certain plant families and genus may be related to a possible mechanism of resource partitioning that shapes the structure of the community.